Frequency Of Fibromyalgia Syndrome And Effects of the Pain Distribution on the Quality of Life In Hospitalized Cancer Patients - Sibel Eyigör,; Hale Karapolat,; Onur Kıvılcım Korkmaz,; Can Eyigör,; Rüçhan Uslu,; Berrin Durmaz,; Meltem Uyar, (Archives of Rheumatology, 2007)
Objective: Even though knowledge on palliative care cumulates, our experience on the symptoms affecting the quality of life among hospitalized cancer patients is still limited. Therefore, we planned to explore the frequency of Fibromyalgia Syndrome (FMS) among hospitalized cancer patients and address the relation between pain, fatigue and quality of life with regard to the extent of pain. Patients and Methods: One hundred and twenty two hospitalized cancer patients were included in this study. Data on demographics, pain (visual analog scale, verbal scale), sleep quality, disease impact (Fibromyalgia Impact Questionnaire -FIQ), fatigue (Brief Fatigue Inventory-BFI), quality of life (Short Form 36 [SF36], and the European Organization for Research and Treatment of Cancer [EORTC QLQ-C30]) were gathered using standard measures. According to the extent of pain, hospitalized cancer patients were divided into three groups; widespread pain, regional pain, no pain. Results: Thirteen of the hospitalized cancer patients (10.7%) included in the study were diagnosed with FMS. There were no statistically significant differences among the three pain groups, with respect to demographic characteristics (p>0.05). There were, on the other hand, significant differences among groups with regard to the presence of metastasis, fatigue, sleep disorder, pain, BFI, FIQ, physical function, bodily pain, general health, vitality, social function, and mental health sub-scores of SF36, and EORTC-QoL-C30 scores (p<0.05). Conclusions: In the present study, we have calculated the frequency of FMS among patients admitted to the oncology hospital in addition to establishing the relations between intensity of pain, fatigue, and quality of life with regard to the physical extent of pain. We believe that the descriptive data presented in this study would be helpful in future studies and therapeutic approaches. (Rheumatism 2007; 22: 126-31)